Knowledge-based intelligent system advancements : systemic and cybernetic approaches - Jozefczyk, Jerzy, 1956-; Orski, Donat, 1971- (Hershey, P.A. : Information Science Reference)
Includes bibliographical references (p. 438-466) and index